Analisis Faktor-Faktor Penentuan Struktur Modal pada Perusahaan Manufaktur di BEI Tahun 2018-2021 - Rowiyani Rowiyani; Khoerul Sholeh; Jayus Jayus; Nikmatul Jannah (Journal Of Business, Finance, and Economics (JBFE), 2022)
The aim of this research is to determine the influence of asset structure, profitability and growth rate on the capital structure of manufacturing companies that go public on the IDX. The population of this research is all financial reports of manufacturing companies on the Indonesia Stock Exchange in 2018-2021. Meanwhile, the sample used was manufacturing companies that had complete financial reports for 2018-2021 and were listed on the IDX and a total of 32 companies were obtained using the purposive sampling method. The data analysis tools used include hypothesis testing and multiple regression analysis. The results of testing hypothesis 1 (H1) state that asset structure has an influence on the increase in the company's capital structure. The results of testing hypothesis 2 (H2) state that profitability has an influence on increasing the company's capital structure. And testing hypothesis 3 (H3) states that company growth has an influence on increasing the company's capital structure. The adjusted R square test states that asset structure, profitability and growth rate have an influence of 58.6% on the company's capital structure, while 41.4% is influenced by other variables not examined.